2023
DOI: 10.1093/aje/kwad214
|View full text |Cite
|
Sign up to set email alerts
|

Suicide Mortality Among Formerly Incarcerated People Compared With the General Population in North Carolina, 2000–2020

Kate Vinita Fitch,
Brian W Pence,
David L Rosen
et al.

Abstract: We aimed to compare rates and characteristics of suicide mortality in formerly incarcerated people to the general population in North Carolina (NC). We conducted a retrospective cohort study of 266,400 people released from NC state prisons between January 1, 2000 and March 1, 2020. Using direct and indirect standardization by age, sex, and calendar year, we calculated standardized suicide mortality rates and standardized mortality ratios comparing formerly incarcerated people to the NC general population. We e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 58 publications
0
9
0
Order By: Relevance
“…Using Excel version 2401 (Microsoft Corp), we applied published formulas for the variance of CMRs and SMRs and Taylor expansion formulas for the variance of other ratios, and then we ran random-effects restricted maximum likelihood (RE-ML) meta-analyses using RStudio 4.3.2 (RStudio Team). We built 10 jurisdictional estimates from 8 adult incarceration studies identified in the 2023 meta-analysis by Janca et al plus 3 studies we identified . All studies were dominated by decades-old data.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Using Excel version 2401 (Microsoft Corp), we applied published formulas for the variance of CMRs and SMRs and Taylor expansion formulas for the variance of other ratios, and then we ran random-effects restricted maximum likelihood (RE-ML) meta-analyses using RStudio 4.3.2 (RStudio Team). We built 10 jurisdictional estimates from 8 adult incarceration studies identified in the 2023 meta-analysis by Janca et al plus 3 studies we identified . All studies were dominated by decades-old data.…”
Section: Methodsmentioning
confidence: 99%
“…We built 10 jurisdictional estimates from 8 adult incarceration studies 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 identified in the 2023 meta-analysis by Janca et al 5 plus 3 studies we identified. 22 , 23 , 24 All studies were dominated by decades-old data. All except 3 studies 14 , 20 , 24 gave partial information on suicide timing in the 2 years after release.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations